If you mean (a-b+c)^2, then...
a^2 - ab + ac - ab + b^2 - bc + ac - bc + c^2
= a^2 + b^2 + c^2 - 2ab + 2ac - 2bc.
Chat with our AI personalities
'a' minus 'b' whole cube is equal to 'a cube' minus 'b cube' minus (3 a square b ) plus (3 a b square) . .. .....thanks
a square plus 2ab plus b square
X2+5x-6. a=1, b=5, and c=-6 The formula is: -b plus or minus the square root of b squared minus 4ac all over 2a. -b+square root of b2-4ac ---- 2a -5 plus or minus the square root of 5 squared minus 4(1)(-6) -5 plus or minus the square root of 25-4(-6) -5 plus or minus the square root of 25+24 -5 plus or minus the square root of 49 -5 plus or minus 7 Here is where you split into two different answers: Number 1: -5 plus 7= 2 Number 2: -5 minus 7= -12 Your answer is X=2, -12
a2+b2+c2-2ab+2bc-2ca
(a+b)cube = a cube + b cube + 3a square b + 3ab square